Knowledge, Obstacles and Options for Implementing Active Learning: A Descriptive Cross-sectional Study from a Medical College in Central Nepal - Anwer Khan, Gulam; Shrestha, Amit; Timilsina, Sameer; Gautam, Ajeevan; Shakya, Shuvechha (Journal of Karnali Academy of Health Sciences, 2022)
Introduction: Education is a dynamic process that needs periodic refining. Lack of innovativeteaching techniques in academics make medical education inadequate in making a significant stridetowards the future. Didactic lectures (DL) have been the gold standard and the most commonmethod of traditional teaching and learning practice. Active learning improves knowledge-sharingprocess facilitate development of analytical approaches to a problem solving and develops criticalthinking. The aim of this study is to evaluate the knowledge, obstacles and options implementingactive learning for among current teaching faculties of different affiliation.Methods: A descriptive, cross-sectional study was conducted on August 2022 among seventy-eightstudy participants. They were instructed to fill in the preformed proforma after obtaining writtenconsent. Statistical analysis done using SPSS.Results: Fifty-two (66.7 percent) of participants strongly favored that active learning imparts bettercontent knowledge, with forty-six (59 percent) of participants strongly agreeing that lack ofinsufficient student-teacher interaction is obstacle for active learning. Forty-four (56.4 percent)participants strongly agreed that group work facilitates active learning.Conclusion: Active learning methods can be implemented in the medical curriculum as medicaleducators are aware of the challenges and obstacles of this teaching learning method. It can developlifelong learning skills among the students and teachers.